How are progression decisions made following external randomised pilot trials? A qualitative interview study and framework analysis - Mellor, K; Dutton, SJ; Hopewell, S; Albury, C (BioMed Central, 2022)
Background External randomised pilot trials help researchers decide whether, and how, to do a future definitive randomised trial. The progression criteria are often prespecified to inform the interpretation of pilot trial findings and subsequent progression decision-making. We aimed to explore and understand the perspectives and experiences of key stakeholders when making progression decisions following external pilot trials.